Give peace a chance on violence and warfare in prehistory and why it matters - Fontijn, D.R (2021)
How is it possible that people kill each other? And above all: how is it possible that people who are able to peacefully live with each other at one moment, can kill each other at another one? These are fundamental questions about the human condition - questions that religions, philosophers and scientists have been wanting to solve since times immemorial and that continue to fascinate us today (Browning 1998; Harrison 1995; Morris 2015). So you may perhaps be wondering why I am posing such deep and essential questions at the start of a lecture that is meant to tell you something about our prehistory?